Dietary carbohydrate intake and risks of overall and 21 site-specific cancers: a prospective cohort study - Chen, Shuhui; Hua, Baojie; Liu, Bin; Wang, Le; Yuan, Qi; Yang, Yudan; Sun, Xiaohui; Ye, Ding; Du, Lingbin; Mao, Yingying; Li, Jiayu (Frontiers in Nutrition, 2025)
BackgroundCancer is among the world’s top causes of death, and diet plays an important role in cancer risk. However, few studies have addressed a comprehensive atlas that details the connections between dietary carbohydrates and cancer risk.MethodsWe conducted a large population-based prospective cohort research based on the UK Biobank including 194,388 participants. The Oxford WebQ, a web-based 24-h recall questionnaire, was used to collect dietary information of each study participant. Using the Cox proportional hazards model, we calculated the hazard ratios (HRs) with 95% confidence intervals (CIs) for the associations of energy-adjusted carbohydrates intake and the incidence of overall cancer as well as 21 site-specific cancers.ResultsA total of 19,990 incidences of cancer (excluding non-melanoma skin cancer) were recorded with a median follow-up of 12.8 years. Energy-adjusted fiber was associated with a reduced risk of overall cancer [HR per IQR increase (95% CI): 0.97 (0.96, 0.99); PFDR: 0.045] and esophageal [0.79 (0.68, 0.91); 0.024], colorectal [0.92 (0.87, 0.97); 0.025], lung [0.87 (0.81, 0.94); 0.014], and kidney cancer [0.85 (0.76, 0.94); 0.031]. Energy-adjusted free sugars were tied to a higher risk of lung [1.12 (1.05, 1.19); 0.024] and kidney cancer [1.15 (1.05, 1.26); 0.039], while non-free sugars were associated with a reduced risk of overall cancer [0.97 (0.95, 0.99); 0.031], colorectal [0.89 (0.84, 0.94); 0.006] and lung cancer [0.86 (0.79, 0.93); 0.014]. Finally, energy-adjusted sucrose was associated with an elevated risk of both lung cancer [1.10 (1.04, 1.17); 0.024] and non-Hodgkin lymphoma [1.15 (1.07, 1.23); 0.008].ConclusionIncreased consumption of dietary fiber and non-free sugars is associated with a reduced risk of certain cancers (e.g., overall cancer, esophageal, colorectal, lung, and kidney cancers), potentially due to their anti-inflammatory effects, short-chain fatty acid production, and other protective mechanisms. In contrast, higher intakes of free sugars and sucrose are associated with an elevated risk (e.g., lung, kidney cancer, and non-Hodgkin lymphoma), which may be attributed to inflammation and oxidative stress.